Предмет: Алгебра,
автор: marisameowkiss2
Упростить1) (6а - b) - (2a + 3 b)
2) 7x + 3y - (-3x + 3y)
3) 8x - (3x - 2y) - 5y
Ответы
Автор ответа:
2
Объяснение:
1) (6a - b) - (2a + 3b) = 6a -b -2a-3b = 6a-2a-b-3b = 4a-4b = 4(a-b)
2) 7x + 3y - (-3x + 3y) = 7x+3y+3x-3y = 10x
3) 8x - (3x - 2y) - 5y = 8x-3x+2y-5y = 5x-3y
Похожие вопросы
Предмет: Английский язык,
автор: kafkaknowzz
Предмет: Другие предметы,
автор: elenakorzh200450
Предмет: Українська мова,
автор: morozandri20
Предмет: Литература,
автор: Лоолчик
Предмет: Математика,
автор: яяя453